Case study review of advanced water metering applications in South Africa - Ngabirano, Lillian (Urban Water Management, 2018)
Advanced water metering is part of a much larger movement towards smart networks and intelligent infrastructure. However, where advanced metering technology is focused more towards the need to obtain meter readings without human intervention in other parts of the world, in South Africa and other developing countries, advanced water metering (in the form of prepaid meters or water management devices) has been developing along a parallel path, driven by the need to provide services to previously unserved communities and deal with the problems caused by rapid urbanisation. In this report, conventional water metering is defined as systems using water meters that display their readings on the meters themselves and advanced water metering as systems that add additional components or functionality to a metering system. Advanced metering has the potential to provide substantial benefits if appropriately applied. However, compared with conventional metering, these systems are considerably more expensive and complicated, and often rely on technology that is still being developed. Advanced metering systems therefore carry a higher risk of failure, poor service delivery and financial losses unless the system is implemented with careful design and thorough planning. This report describes a number of case studies of the application of advanced metering in South Africa. The case studies were evaluated according to the evaluation framework described in Appendix A and their detailed evaluations are included in each relevant chapter. Evaluations were done in four areas: technical, environmental, social and economic. The technical evaluation is based on the systems complying with the relevant national metering standards and good metering practice, the environmental evaluations on battery disposal and water savings and the social evaluation on broad socio-economic indicators. It should be recognised that social issues are particularly complex and that no general evaluation framework can accurately predict whether an advanced metering system will be accepted by a particular community. The economic evaluations were based on reductions of the current system cost and not absolute values. Economic performance indicators included the effective surplus (income minus expenses over averaged over the meter service life) and capital repayment period. An overview of lessons learned and conclusions from the case studies are provided in Chapters 8 and 9 of the report.